Efektivitas Pembelajaran Daring Bimbingan Konseling Pada Siswa Sekolah Menengah Pertama - Sara Sahrazad; Maria Cleopatra; Lusiana Wulansari; Dellia Mila Vernia (Peneliti.net, 2021)
Online learning is an alternative learning that is carried out during the Corona pandemic season. Although not as unbalanced as expected, this learning needs to be done, in order to reduce the number of corona patients. The aim of this research is to describe the effectiveness of the learning of the junior high school students' counseling guidance subject. The method used is a qualitative method. Researchers take data from students through online interviews, photos, and questionnaires. The data is processed by sorting the data, and analyzing the data. The data were taken from SMP Bani Taqwa Bekasi. A total of 21 junior high school students grade VII and VIII The results showed that online learning guidance counseling online learning in BK subjects at Bani Taqwa Middle School went quite well, 74% of students were happy to follow online, learning had used the right online application, students could argue constraints well ,. There is a good two-way communication. However, there are still some obstacles and problems. There are 26% who do not feel happy learning darng, this is due to several factors such as boredom, readiness to use applications, internet networks and the ability to use online applications. The author suggests that online application training is needed, additional rest hours, increased interesting learning as well as a continuous learning program.